2009
DOI: 10.1007/978-3-642-04346-8_28
|View full text |Cite
|
Sign up to set email alerts
|

Superimposed Image Description and Retrieval for Fish Species Identification

Abstract: Fish species identification is critical to the study of fish ecology and management of fisheries. Traditionally, dichotomous keys are used for fish identification. The keys consist of questions about the observed specimen. Answers to these questions lead to more questions till the reader identifies the specimen. However, such keys are incapable of adapting or changing to meet different fish identification approaches, and often do not focus upon distinguishing characteristics favored by many field ecologists an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…We confirmed that participants engaged in two broad activities within fish identification -learning about a species and identifying species (found in our previous evaluation [12] as well). Sometimes both activities would happen simultaneously as a participant tried to identify an unknown specimen and then learn about its details.…”
Section: Context and Strategies That Suggest Working With Subimages Isupporting
confidence: 88%
See 4 more Smart Citations
“…We confirmed that participants engaged in two broad activities within fish identification -learning about a species and identifying species (found in our previous evaluation [12] as well). Sometimes both activities would happen simultaneously as a participant tried to identify an unknown specimen and then learn about its details.…”
Section: Context and Strategies That Suggest Working With Subimages Isupporting
confidence: 88%
“…Experienced users would give us wider exposure to types of users in the fisheries domain as compared to the earlier classroom evaluation [12]. In that evaluation, the participants were undergraduate students, who were relatively new to fisheries and to fish identification.…”
Section: Study Design and Setupmentioning
confidence: 98%
See 3 more Smart Citations